Perspective of Labor Regulation of Sex Work in Colombia - Delgado-Beltran, Jairo Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article develops the main jurisprudential concepts on the labor relationship derived from the sex trade, and from them, it exposes the most relevant aspects in the approach to the regulation of sex work in Colombia, based on the decisions of the Constitutional Court (Sentence T - 594 of 2016 and T 073 of 2017) and the conceptual and academic developments in Colombia. The methodology applied for the collection of information and verification of the results was carried out through workshops, application of analytical surveys of perception of the activity, conducting interviews and socio-legal care for female sex workers and social organizations that group them. Among other aspects is that, Colombian labor law does not have enough elements to regulate the activity. International labor and human rights law is protectionist in a regulation of sex work. Women's human rights, and particularly constitutional block conventions, are necessary to regulate sex work.